Optical Properties and Sequence Information of Tin‐Centered Conjugated Microporous Polymers. Issue 7 (28th December 2017) - Uptmoor, Andrea C.; Ilyas, Ruben; Elbert, Sven M.; Wacker, Irene; Schröder, Rasmus R.; Mastalerz, Michael; Freudenberg, Jan; Bunz, Uwe H. F.
Abstract: We synthesized conjugated microporous polymers (CMPs) based on tetrakis(4‐ethynylphenyl)stannane and diiodobenzene as tectons, using Sonogashira couplings under different conditions. Through variation of the reaction conditions (catalysts, bases and solvents), appearance, surface area and emission properties of the formed CMPs were significantly altered. Wet‐chemical, acid‐mediated digestion and analysis of the resulting struts of these otherwise insoluble networks give insight into the molecular setup. Abstract : Digested ! A series of fluorescent tin‐cantered microporous polymers was synthesized by Sonogashira–Hagihara coupling. Fluorescence and surface area can be tuned by adjusting the reaction conditions. Digestion with chloroacetic acid also allows for wet‐chemical analysis of the organic linker situated between the tin centers. Sequence analysis is therefore achieved.